Open Source, Open Vision: The MakerPro Network and the Broadening of Participation in Setting Taiwan's IT Vision Agenda. (2nd September 2019) - Freeman, Guo; Bardzell, Jeffrey; Bardzell, Shaowen
Abstract : HCI recognizes the importance of visions as both a design and futuring approach and a problem-solving technique. One challenge of visioning work is who can propose and shape IT visions and how they can achieve the widespread buy-in needed to make them efficacious. In this paper, we focus on the potential of making, open design, and open manufacturing for contributing toward, if not fully achieving, the broadening of participation in IT envisioning. We use Taiwan's MakerPro, a manufacturers and IT R&D community as a case to unpack what collective IT visioning looks like, how it shapes IT agendas concretely, and the implications for open design/open manufacturing research agenda in HCI. Our findings reveal how MakerPro members constructed and developed visions for open design and open manufacturing in Taiwan, obstacles to such visions, and how these obstacles can be collaboratively overcome through a participative and even democratic process. We also show that the collective purposiveness not only defines a regional vision agenda but also embraces an entire nation's future.